Multiparticulate Drug Delivery of Losartan Potassium via Extrusion-Spheronization: Formulation and Dissolution Comparisons - Vishal D. Yadav; Dipali S. Salunkhe; Vasant Y. Lokhande (BIO Integration)
Background: Losartan potassium, an antihypertensive medication, has high solubility and a short half-life that result in potential adverse effects and rapid drug clearance. Multiparticulate drug delivery systems enhance the drug’s bioavailability, decrease patient-to-patient variability, and optimize drug distribution. Herein, losartan potassium pellets for sustained drug release were developed and characterized. Methods: The formulation process involved varying the concentrations of Eudragit RSPO (200 mg, 400 mg, or 600 mg) and Eudragit L100 (200 mg, 400 mg, or 600 mg) across nine pellet batches, and adjusting the triethyl citrate concentrations accordingly. The pellets’ bulk density, tapped density, flow properties (Carr’s index, Hausner’s ratio, and angle of repose), drug content, particle size distribution, and in vitro drug release were evaluated. Interactions between losartan potassium and the excipients were analyzed with FTIR and DSC. Results: FTIR spectra indicated physical interactions without major chemical alterations, whereas DSC thermograms revealed changes in thermal behavior due to excipient interactions. In vitro drug release studies indicated that formulations with higher concentrations of Eudragit RSPO and triethyl citrate achieved controlled, prolonged drug release. The optimized batch (F7) demonstrated balanced characteristics including favorable bulk and tapped density, good flow properties, and a sustained release profile. Varying the polymer and plasticizer concentrations significantly influenced pellet performance, and F7 was found to be the most promising formulation for sustained-release applications. Conclusion: This study underscores the importance of polymer selection and formulation optimization in developing effective sustained-release drug delivery systems, and has potential implications for enhancing therapeutic outcomes in clinical practice.